Multidisciplinary Technology of Animatronics: A Review - Utture, Omkar; Mane, Nikhil S.; Varute, Shubham S.; Waingade, Asawari B. (Asian Review of Mechanical Engineering, 2017)
Animatronics is a developing technology which involves the disciplines of Mechanical Engineering, electronics engineering and animations to produce real life size replicas of the object working on robotic technology. Animatronics technology creates animated objects working on mechanisms which will seems and sense alive. These objects are more realistic compare to the robotic machines. The basic mechanism of these machines is a combination of different mechanical and electronic components. They can be powered by electrical motors, pneumatics or hydraulics, and their controlling mechanism can be manual controlled or computer controlled. The animatronics objects are made of mechatronics structure with fully functional and controlled mechanisms covered with detailed and colored skins. The alive nature of the animatronics object is result of artistically designed costuming of the object. Animatronics provide real life mirage to the non living structures. This paper provides review on different aspects of animatronics like. In this work, wide overview of animatronics with different present and future applications of the field of animatronics is rectified.